Analisis Dampak Work from Home terhadap Stres Kerja, Adaptive Performance dan Kinerja Pegawai - Hamdani Hamdani; Hadi Sunaryo; Pardiman Pardiman (IQTISHODUNA, 2022)
The present research is set out to reveal the impact of changing work patterns from WFO to WFH at UIN Maulana Malik Ibrahim Malang, with the specific purpose of analyzing the impact of WFH on work stress, adaptive performance, and employees’ performance. This research utilizes a quantitative approach. The sampling technique employed is saturated sampling in which the entire population – 130 people – were used as respondents. Both primary and secondary data were analyzed quantitatively using Structural Equation Modeling or Structural Equation Model with the help of AMOS software. The results demonstrated that there was a significant positive effect of WFH on work stress and adaptive performance among the respondents–the support staff of UIN Maulana Malik Ibrahim Malang – and there was no significant effect of WFH on employees’ performance.